The potential antiepileptogenic effect of neuronal Cx36 gap junction channel blockage - Wang Guangliang; Wu Xuemei (Translational Neuroscience, 2021)
Epilepsy is one of the most prevalent neurological disorders and can result in neuronal injury and degeneration. Consequently, research into new antiepileptic drugs capable of providing protection against neuronal injury and degeneration is extremely important. Neuronal Cx36 gap junction channels have been found to play an important role in epilepsy; thus, pharmacological interference using Cx36 gap junction channel blockers may be a promising strategy for disrupting the synchronization of neurons during seizure activity and protecting neurons. Based on these promising findings, several in vivo and in vitro studies are ongoing and the first encouraging results have been published. The results bring hope that neurons can be protected from injury and degeneration in patients with epilepsy, which is currently impossible.